Suitability of the Carbonate Rocks of the Bekhme Formation Exposed in Shakrook Anticline, Iraqi Kurdistan region, for Cement Industry - Hamwandy, Mohammed J.; Ibrahim, Rahel Kh.; Sissakian, Varoujan K. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2022)
The Bekhme Formation forms almost the bulk of the Shakrook anticline, especially the limbs. The current research deals with studying the exposed beds within the Bekhme Formation at the Shakrook anticline to check the suitability of the exposed rocks at the northeastern limb of the anticline for the cement industry. Twenty rock samples from a section which lies along a deeply cut valley that crosses the northeastern limb of the Shakrook anticline within the Bekhme Formation were collected. The channel sampling method was applied; therefore, each sample represents the concerned sampling interval and to be representative for the thickness of the sampled interval. The total thickness of the sampled section is 110 m with a covered interval of 15 m, totaling to 125 m. The collected 20 samples were prepared at the laboratory of the Koya University and were subjected to XRF test at the Tarbiat Modares University, Iran, to indicate the concentration of the main oxides (CaO, MgO, Al2O3, Fe2O3, Na2O, K2O, and SO3), and Cl and L.O.I. The indicated concentrations at each sample, from both universities, were compared and were found to be almost coinciding. The average concentrations at each sample were changed to weighted averages and the results were compared with the Iraqi standards for cement industry. The results revealed that the sampled rocks are excellent for cement production.